In vitro experimental infection of primary human hepatocytes with hepatitis B virus - Galle, Peter R.; Hagelstein, Jens; Kommerell, Burkhard; Volkmann, Martin; Schranz, Peter; Zentgraf, Hanswalter (Gastroenterology, 1994)
Background/Aims: Studies on the interaction of hepatitis B virus (HBV) with its host cell require a suitable tissue culture system. This study used primary adult hepatocytes from healthy human liver tissue to establish productive infection in vitro. Methods: Hepatocytes were inoculated overnight with HBV. Production of viral proteins was assessed by radioimmunoassay and by [35S]methionine labeling, and production of viral DNA was assessed by Southern blotting and endogenous polymerase assay. Results: Secretion of high levels of hepatitis B surface antigen (HBsAg) and low levels of hepatitis B virus e antigen (HBeAg) into the medium was detectable 6 days after infection and reached maximum values after 12 days. Metabolic labeling showed production of viral proteins to be a result of de novo synthesis. The appearance of single-stranded HBV DNA in the cytoplasm of infected cells, typically present in immature cores, indicated viral replication. HBV DNA containing particles possessing an active viral DNA polymerase could be immunoprecipitated from the medium 12 days after infection. An antiserum specific for the preS1 region of the viral envelope was capable to block infection. Presence of dimethyl sulfoxide in the medium greatly improved the yield of viral proteins. Conclusions: Primary adult human liver cells are competent for infection with HBV.